Service Quality of Private Hospitals: The Patient's Assessment (A Case STudy of Meerut District) - Jain, Sapna (Journal of Commerce and Trade, 2018)
The World is changing very fast. since, the inception of LPG, the demand for services has increased unexpectedly. Thus, service sector has become a rapidly growing area of the world economy and the health services organisations play an important role in such growth. In a decade or so, the rise and growth of private hospitals providing various health care services in India and in Meerut as well. With the opening of more than 200 medical care centres or hospitals. The health care market has grown and turn out to be a competitive affair. This study is exploratory by nature, which holds light of quality gaps in our health care sector, which can be worked upon to make the patients more comfortable and happy. However, some criteria like severity of illness, doctor's characteristics and treatment were not taken into consideration which could have an impact on the responses given. Classification-JEL : I11, I15, L33, L97.